PEMBELAJARAN KERAJINAN MENURUT KURIKULUM MUATAN LOKAL DI SLTP PENYELENGGARA PROGRAM KETERAMPILAN KERAJINAN DJ YOGYAKARTA - Martono Martono (LPMPP Universitas Negeri Yogyakarta, 2001)
In developing the quality l?!'teaching crqfis in junior high school, LPM Universitas NegeriYogyakarta through the school developing program has done development which resulteddecreasing the gap jelt by the school. This program was done in the form f leaming activity,which has done by developing team from LPM UNY to the teachers and students in the school.Teachers as the prin1ary target of'handicraft skill development, in the next time are hoped thereis good improving the teaching crafts in the school it self. The actuating ofthe handicraft skillsin the class use the material that has outlined in the curriculum developed with local culturalmaterial. The aims ofteaching crqfts principally were to teach esthetic value, work appreciationthe basic offorming work ethos, the appreciation product toward teacher and student. Thetraining aims to analyze the curriculum ojj'unior high school crajis related the local culturalpotential,The teaching crafts in the class uses the materials guided in the curriculum that aredeveloped using the local culturallnaterials. The teaching materials involve: 1) wood crafts thatconsists oj